Alexandrian Cosmopolitanism : An Archive - Halim, Hala (Book collections on Project MUSE., 2013)
This book argues that the narrative of Alexandria's cosmopolitanism was in tune with colonial modernity. The Alexandria Archive is a comparative study of representations of cosmopolitanism in texts by C.P. Cavafy, E.M. Forster, Lawrence Durrell, and Bernard de Zogheb from the late nineteenth century to the late twentieth century.